2021
DOI: 10.1166/jnn.2021.18962
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ZnO/Carbon Xerogel Composite as a Photocatalyst for Solar and Visible Light Degradation of the Rhodamine B Dye

Abstract: This study is focused on the evaluation of the Rhodamine B photodegradation using ZnO/carbon xerogel composite as a photocatalyst, in order to enhance the photocatalytic process efficiency under visible light. The proposed synthesis employs tannin as a precursor for the carbon xerogel, which enhances the economic and environmental aspect of the composite. The synthesized materials have the hexagonal structure of the zinc oxide (wurtzite), which is homogeneously distributed on the carbonaceous matrix. The diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…ZnO/carbon xerogel composite were prepared using tannin as carbon source [93]. The diffuse reflectance test demonstrated that light absorption was significantly enhanced for the composite, while the solar light-driven photodegradation tests revealed that the synthesized composite achieved almost complete degradation of Rhodamine B.…”
Section: Biomass and Waste As Sources Of Carbonmentioning
confidence: 99%
“…ZnO/carbon xerogel composite were prepared using tannin as carbon source [93]. The diffuse reflectance test demonstrated that light absorption was significantly enhanced for the composite, while the solar light-driven photodegradation tests revealed that the synthesized composite achieved almost complete degradation of Rhodamine B.…”
Section: Biomass and Waste As Sources Of Carbonmentioning
confidence: 99%
“…On the other hand, the incorporation of carbonaceous materials into the system, such as carbon xerogels (CX), can help reduce this drawback. These materials exhibit desirable intrinsic properties for photocatalytic reactions, such as high surface area, high absorption of visible radiation, and high conductivity, which can act as electron reservoirs (Moraes et al 2022;Cunha et al 2021;Santos et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Como esperado, a Figura 85 mostra que os materiais XCL/ZnO 1.0 e XCL/ZnO-Bi2O3 5% apresentam uma maior capacidade de absorver radiações de menor energia, quando comparados ao óxido de zinco puro. Como discutido anteriormente, esse comportamento é derivado da presença da fase carbonosa no material e pode levar à uma maior atividade dos compósitos quando submetidos à processos baseados em radiação natural (Santos et al, 2021).…”
Section: Espectroscopia De Refletância Difusa (Xcl/zno-bi2o3 X%)unclassified